Social sustainability, past and future : undoing unintended consequences for the earth's survival - Leeuw, Sander Ernst van der (Cambridge : Cambridge University Press, 2020)
In this book, Sander Van der Leeuw examines how the modern world has been caught in a socio-economic dynamic that has generated the conundrum of sustainability. Combining the methods of social science and complex systems science, he explores how western, developed nations have globalized their world view and how that view has led to the sustainability challenges we are now facing. Its central theme is the co-evolution of cognition, demography, social organization, technology and environmental impact. Beginning with the earliest human societies, Van der Leeuw links the distant past with the present in order to demonstrate how the information and communications technology revolution is undermining many of the institutional pillars on which contemporary societies have been constructed. An original view of social evolution as the history of human information-processing, his book shows how the past offers insight into the present, and can help us deal with the future. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 16 Dec 2019).
Keywords: Environmental sociology; Sustainability -- Social aspects; Environmentalism -- Social aspects; Sustainable development -- Social aspects